Evolution of Literary-Critical Method of Julius Aikhenvald and His Views on Shakespeare’s Creativity - V. V. Serdechnaya; D. N. Zhatkin (Научный диалог)
The research problem concerns the evolution of critical views of Julius Isaevich Aikhenvald (1872—1928) in relation to his perception of William Shakespeare’s creativity. The aim of the study is to trace how changes in the critic’s personal fate and the global political situation led to his reevaluation of Shakespeare’s images. The material consists of little-known articles by the critic, published both in Russia in the 1910s-1920s and in emigration (mainly in the emigrant newspaper “Rul”). Hermeneutical, historical-cultural, and comparative methods were used for the research. It is established that in the pre-revolutionary period, Julius Aikhenvald, following his subjective immanent method of criticism, evaluates Shakespeare as a universal genius (in particular, comparing him to Leo Tolstoy). The most important characteristic becomes the universality of the playwright’s artistic attention, allowing to reflect all aspects of existence, beyond any hierarchies. In particular, Aikhenvald implicitly speaks about Shakespeare’s moral relativism. However, in the emigrant period, using Shakespeare’s images (primarily the images of Caliban and Coriolanus) to analyze the historical situation in the USSR, he comes to affirm the objectivity of good and truth as characteristics of literature and social reality.